Prevotella intermedia and Porphyromonas gingivalis in dental caries with periapical granuloma - Risya Cilmiaty; Afiono Agung Prasetyo; Khilyat Ulin Nur Zaini; Mandojo Rukmo; Suhartono Taat Putra; Widya Asmara (Dental Journal (Majalah Kedokteran Gigi), 2013)
Background: Dental caries with necrotic pulp is a multifactorial disease that attacks enamel involving tooth pulp. The anaerobic bacteria infection in the pulp chamber could induce the formation of periapical granuloma. However, the presence of the most frequently anaerobic bacteria identified in apical periodontitis, Porphyromonas gingivalis and Prevotella intermedia, in periapical granuloma have not been confirmed. Purpose: The aims of study were to determine the presence of Porphyromonas gingivalis and Prevotella intermedia in dental caries with necrotic pulp and to determine its relation to periapical granuloma. Methods: Thirty-six patients of dental caries with necrotic pulp in Dr. Moewardi General Hospital in Surakarta, Indonesia were involved and classified into two groups, the group of patients with periapical granuloma and the group of patients without periapical granuloma. The caries tooth was extracted, and the chronic periapical tissue was swabbed and cultured on blood agar medium in anaerobic condition. The bacterial DNA was extracted from the positive cultures and subjected for Polymerase Chain Reaction (PCR). Results: Periapical granuloma was more likely found in women (OR 5.5, 95% CI=1.277-23.693; RR 2.5, 95% CI= 1.025-6.100). Black colonies bacteria were associated with periapical granuloma (OR 2.2, 95% CI=0.517-9.594; RR 1.5, 95% CI=0.655-3.623). Porphyromonas gingivalis and Prevotella intermedia were detected in group with or without periapical granuloma, however, only Prevotella intermedia was associated with periapical granuloma (OR 1.6, 95% CI=0.418-5.903; RR 1.3, 95% CI=0.653-2.393). Conclusion: The presence of Porphyromonas gingivalis and Prevotella intermedia in periapical granuloma were confirmed, however, only Prevotella intermedia were associated with periapical granuloma.Latar belakang: Karies gigi dengan pulpa nekrosis adalah penyakit multifaktorial yang menyerang enamel hingga ruang pulpa gigi. Infeksi bakteri anaerob di pulpa nekrosis dapat menginduksi pembentukan granuloma periapikal. Namun, keberadaan bakteri anaerob yang paling banyak ditemukan di periodontitis apikal, Porphyromonas gingivalis dan Prevotella intermedia, di granuloma periapikal masih perlu diteliti . Tujuan: Penelitian ini bertujuan meneliti keberadaan bakteri Porphyromonas gingivalis dan Prevotella intermedia, di karies gigi dengan pulpa nekrosis dan menganalisis kaitannya dengan granuloma periapikal. Metode: Tiga puluh enam pasien karies gigi dengan pulpa nekrosis di Rumah Sakit Umum Dr. Moewardi di Surakarta Indonesia dilibatkan dan diklasifikasikan dalam dua kelompok yaitu kelompok pasien dengan granuloma periapikal dan kelompok pasien tanpa granuloma periapikal. Gigi karies diekstraksi dan jaringan periapikal kronis diusap dan dikultur di media agar darah dalam kondisi anaerob. DNA bakteri diekstrak dari kultur yang positif dan dilakukan pemeriksaan dengan Polymerase Chain Reaction (PCR). Hasil: Granuloma periapikal lebih banyak ditemukan pada wanita (OR 5,5, 95% CI= 1,277-23,693; RR 2,5, 95% CI= 1,025-6,100). Koloni bakteri berwarna hitam diasosiasikan dengan granuloma periapikal (OR 2,2, 95% CI= 0,517-9,594; RR 1,5, 95% CI= 0,655-3,623). Porphyromonas gingivalis dan Prevotella intermedia terdeteksi di jaringan karies dental dengan atau tanpa granuloma periapikal, namun hanya Prevotella intermedia yang diasosiasikan dengan granuloma periapikal (OR 1,6, 95% CI= 0,418-5,903; RR 1,3, 95% CI= 0,653-2,393). Simpulan: Porphyromonas gingivalis dan Prevotella intermedia ditemukan di granuloma periapikal, namun hanya Prevotella intermedia yang terkait langsung dengan granuloma periapikal.